2017
DOI: 10.1073/pnas.1620140114
|View full text |Cite
|
Sign up to set email alerts
|

Tunable moiré bands and strong correlations in small-twist-angle bilayer graphene

Abstract: According to electronic structure theory, bilayer graphene is expected to have anomalous electronic properties when it has long-period moiré patterns produced by small misalignments between its individual layer honeycomb lattices. We have realized bilayer graphene moiré crystals with accurately controlled twist angles smaller than 1°and studied their properties using scanning probe microscopy and electron transport. We observe conductivity minima at charge neutrality, satellite gaps that appear at anomalous ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
408
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(445 citation statements)
references
References 35 publications
16
408
0
4
Order By: Relevance
“…For small twist angles and latticeconstant mismatches, heterostructures exhibit long period moiré patterns that can yield dramatic changes. Moiré pattern formed in graphene-based heterostructures has been extensively studied, and many interesting phenomena have been observed, for example gap opening at graphene's Dirac point [1,2], generation of secondary Dirac points [3,4] and Hofstadter-butterfly spectra in a strong magnetic field [1,5,6].In this Letter, we study the influence of moiré patterns on collective excitations, focusing on the important case of excitons in the transition metal dichalcogenide (TMD) 2D semiconductors [7,8] like MoS 2 and WS 2 . Exciton features dominate the optical response of these materials because electron-hole pairs are strongly bound by the Coulomb interaction [9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For small twist angles and latticeconstant mismatches, heterostructures exhibit long period moiré patterns that can yield dramatic changes. Moiré pattern formed in graphene-based heterostructures has been extensively studied, and many interesting phenomena have been observed, for example gap opening at graphene's Dirac point [1,2], generation of secondary Dirac points [3,4] and Hofstadter-butterfly spectra in a strong magnetic field [1,5,6].In this Letter, we study the influence of moiré patterns on collective excitations, focusing on the important case of excitons in the transition metal dichalcogenide (TMD) 2D semiconductors [7,8] like MoS 2 and WS 2 . Exciton features dominate the optical response of these materials because electron-hole pairs are strongly bound by the Coulomb interaction [9][10][11][12].…”
mentioning
confidence: 99%
“…For small twist angles and latticeconstant mismatches, heterostructures exhibit long period moiré patterns that can yield dramatic changes. Moiré pattern formed in graphene-based heterostructures has been extensively studied, and many interesting phenomena have been observed, for example gap opening at graphene's Dirac point [1,2], generation of secondary Dirac points [3,4] and Hofstadter-butterfly spectra in a strong magnetic field [1,5,6].…”
mentioning
confidence: 99%
“…Utilising this technique, Cao et al 44 This is the authors' version, pre-peer reviewed, of the following article: R. Frisenda et al "Recent progress in the assembly of nanodevices and van der Waals heterostructures by deterministic placement of 2D materials" Chemical Society Reviews (2017) DOI: 10.1039/C7CS00556C Which has been published in final form at: http://pubs.rsc.org/en/content/articlelanding/2017/cs/c7cs00556c 25 and Kim et al 43 reported on h-BN-encapsulated twisted bilayer graphene devices with twist angles equal or smaller than 2º, where insulating states induced by strong interlayer interactions via superlattice modulation were observed. The technique was taken to the current limit by Kim et al 45 where the sub-degree twist angle regime was explored with a resolution better than 0.2º. This is the authors' version, pre-peer reviewed, of the following article: R. Frisenda et al "Recent progress in the assembly of nanodevices and van der Waals heterostructures by deterministic placement of 2D materials" Chemical Society Reviews (2017) DOI: 10.1039/C7CS00556C Which has been published in final form at: http://pubs.rsc.org/en/content/articlelanding/2017/cs/c7cs00556c 26 …”
Section: Control Of the Twisting Angle Between The Stacked Layersmentioning
confidence: 99%
“…By stacking graphene layers together, the properties of monolayer graphene could be tuned due to the evolution of 2D character and the Dirac fermion behavior. A strongly correlated system may be created and allow to study exotic many‐body quantum phases, as demonstrated in the magic‐angle‐twisted bilayer graphene . Li et al found that the band structure of bilayer graphene is sensitive to the stacking orientation, which alters the interlayer coupling between the two graphene sheets .…”
Section: Vertically Stacked Graphene Layersmentioning
confidence: 99%